A Synthesis and Review of Medicinal Uses, Phytochemistry and Pharmacological Properties of Cissampelos mucronata A. Rich. (Menispermaceae) - Alfred Maroyi (Journal of Pharmacy and Nutrition Sciences, 2020)
Cissampelos mucronata A. Rich. is a perennial climber widely used as traditional medicine in tropical Africa. This study is aimed at providing a critical review of medicinal uses, phytochemical and pharmacological properties of C. mucronata. Documented information on medicinal uses, phytochemical and pharmacological properties of C. mucronata was collected from several online sources such as Scopus, Google Scholar, PubMed and Science Direct, and pre-electronic sources such as book chapters, books, journal articles and scientific publications obtained from the University library. The articles published between 1962 and 2020 were used in this study. This study revealed that leaves, rhizome, roots and stems, and whole plant parts of C. mucronata are mainly used as traditional medicines for sexually transmitted infections, fever, swellings, headache, respiratory problems, snakebite, malaria, pregnancy problems and gastro-intestinal problems. Phytochemical compounds identified from the species include alkaloids, anthraquinones, flavonoids, glycerine, glycosides, phenolics, reducing sugars, resin, saponins, steroids, tannins and triterpenes. Pharmacological research revealed that C. mucronata extracts and alkaloids isolated from the species have antibacterial, anti-mycobacterial, antifungal, antiplasmodial, antitrypanosomal, anti-ulcer, anti-androgenic, anti-steroidogenic, enzyme tyrosine kinase p56 inhibitory, hypoglycemic, larvicidal, molluscicidal, sedative, tocolytic, uterine relaxant and cytotoxicity activities. There is need for extensive toxicological evaluations of crude extracts and compounds isolated from the species since C. mucronata contains potentially toxic compounds